La épica imposible de Cervantes. - Canseco, Luis Gómez (Cervantes, 2025)
The epic was undoubtedly the most prestigious literary, courtly and political genre in Golden Age literature. Cervantes was thoroughly familiar with it thanks to his reading between Italy and Algiers. After returning to Spain in 1580, the epic offered him an extraordinary chance to regain lost time and place. Although—as far as we know—he never wrote an epic text, the genre, in its different versions, was decisive in the construction of an original literature. The purpose of these pages is to analyze this link in the history and evolution of Cervantes' writing.